Examining the relationship between poor sleep health and risky driving behaviors among college students. (5th November 2021) - Robbins, Rebecca; Piazza, Andrew; Martin, Ryan J.; Jean-Louis, Girardin; Knowlden, Adam P.; Grandner, Michael A.
Abstract: Objective: Risky driving behaviors, such as texting while driving, are common among young adults and increase risk of traffic accidents and injuries. We examine the relationship between poor sleep and risky driving behaviors among college students as potential targets for traffic injury prevention. Methods: Data for this study were obtained from a cross-sectional survey administered to a college student sample in the United States Midwest (n = 1, 305). Sleep was measured using the Pittsburgh Sleep Quality Index (PSQI). Risky driving behaviors were measured, including sending texts/emails; reading texts/emails while driving; talking on the phone while driving; falling asleep while driving; and driving under the influence. Risky driving behavior was defined as a response of "just once, " "rarely, " "sometimes, " "fairly often" or "regularly" (reference = "never"). Logistic regression was used to examine the relationship between sleep and risky driving, after adjusting for confounders. Results: Among participants, 75% reported sending texts/emails while driving, 82% reported reading texts/emails while driving, and 84% reported phone talking while driving; 20% reported falling asleep while driving; 8% reported driving under the influence; and 62% reported 3 or more risky behaviors. Compared to those reporting no sleep disturbance, those with sleep disturbance "once or twice a week" were more likely to report sending a text/email while driving (aOR: 2.9, 95%CI:1.7-4.9), reading a text/email while driving (aOR:3.1, 95%CI:1.5-5.5), talking on the phone while driving (aOR:1.9, 95%CI:1.0-3.4), and falling asleep while driving (aOR:3.4, 95%CI:1.5-7.4). Compared to those reporting no daytime dysfunction, those reporting issues "once or twice a week" were more likely to report talking on the phone while driving (aOR:1.7, 95%CI:1.1-2.7) and falling asleep while driving (aOR:3.6, 95%CI:2.3-5.6). Conclusions: Future research may consider designing behavioral interventions that aim to improve sleep, reduce drowsy driving among young adults.